Design and Characterization of Paclitaxel-Loaded Polymeric Nanoparticles Decorated With Trastuzumab for the Effective Treatment of Breast Cancer - Sakhi, Mirina; Khan, Abad; Iqbal, Zafar; Khan, Ismail; Raza, Abida; Ullah, Asmat; Nasir, Fazli; Khan, Saeed Ahmad (Frontiers in Pharmacology, 2022)
Abstract The aim of the study was to design and formulate antibody mediated targeted, biodegradable polymeric drug delivery system releasing drug in a controlled manner to achieve a therapeutic goal for the effective treatment of breast cancer. Antibody mediated paclitaxel loaded PLGA polymeric nanoformulations were prepared by solvent evaporation method using different experimental parameters and compatibility studies. The optimized formulations were selected for in-vitro and in-vivo evaluation and cytotoxicity studies. The in-vitro drug release studies were carried out using dialysis bag diffusion method. A bi-phasic release pattern was observed for the paclitaxel loaded PLGA nanoparticles showing a burst release for 24 hours followed by an extended release for 14 days, however a more controlled and sustained release was observed for antibody conjugated polymeric nanoparticles. Rabbits were used as experimental animals for the assessment of various in-vivo pharmacokinetic parameters of selected formulations. The pharmacokinetic parameters such as Cmax (1.18-1.33 folds), AUC0-t (39.38-46.55 folds), MRT (10.04-12.79 folds), t1/2(3.06-4.6 folds), and Vd (6.96-8.38 folds) have been increased significantly while clearance (4.34-4.61 folds) has been decreased significantly for the selected nanoformulations as compared to commercially available paclitaxel formulation (Paclixil®). The cytotoxicity of reference drug and paclitaxel loaded PLGA nanoparticles with and without antibody was determined by performing MTT assay against MCF-7 cells. The surface conjugation of nanoparticles with trastuzumab resulted in an increase in-vitro cytotoxicity as compared to plain nanoformulations and commercially available conventional brand (Paclixil®). The developed PLGA-paclitaxel nanoformulations conjugated with trastuzumab have the desired physiochemical characteristics, surface morphology, sustained release kinetics and enhanced targeting. The pharmacokinetic parameters were improved significantly in comparison with commercially available paclitaxel formulations.